Evaluación de alternativas de curado para el concreto en Bogotá (2022)
Due to my experiences on site, I identify the lack of control in the curing of concrete elements, generally due to the need to advance with the works, leaving the importance of this procedure in the background, many times it is because it is not understood how much resistance it can lose the concrete when it is not properly cured. The objective of this monograph is to be able to identify the importance of concrete curing for the development of mechanical properties, to establish curing methods that are viable for works, in addition to obtaining an interval of resistance difference referring to concrete cured in the laboratory and one outdoors to help engineers make decisions regarding the curing of concrete on site. The way in which this thesis will be carried out is by compiling information from different investigations carried out worldwide, regarding the curing of concrete, identifying its importance for the development of the chemical reactions of cement, the affectation in the mechanical properties, in addition, an investigation will be carried out to determine the difference in resistance between a concrete sample cured in the laboratory and another outdoors (in the climate of the city of Bogotá). In the development of this thesis it was possible to conclude that the curing of concrete is vital for the development of the mechanical properties and durability of the concrete, in addition, a difference in resistance could be evidenced in the concrete cured in the laboratory and the other in the open. up to 21%, which is quite considerable.